Pelatihan Pembelajaran IPA Melalui Pendekatan STEM (Science, Technology, Engineering, Mathematic) Bagi Guru SMP Negeri 1 Kota Sungai Penuh - Hendri, Menza; Nehru; Rasmi, Dian Pertiwi; Sirait, Jeliana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Teachers reveal that they have not implemented STEM-based learning because teachers do not have sufficient insights and they do not have the skills to develop STEM-based learning. Therefore, the effort made to over come these problems are providing training on science learning using a STEM approach to improve the competence of science teachers in conducting STEM-based learning in order to improve the quality of learning in the classroom. The training participants are science teachers at SMPN 1 Sungai Penuh City and the place of service at SMPN 1 Sungai Penuh, Kerinci. Through this activity, it is hoped that teachers can get to know the current developments of the 21st century and of course science teacher at SMP Negeri 1 Kota Sungai Penuh can apply a STEM approach in science learning. The impact is for classroom learning to be more active and teachers are able to develop very effective learning tools in accordance with the demands of basic competencies for 21st century skills.